2012
DOI: 10.1074/jbc.m111.330373
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Epigenetic Histone Post-translational Modifications at Type 1 Diabetes Susceptible Genes

Abstract: Background: Both genetic and epigenetic factors are implicated in Type 1 diabetes (T1D). Results: Variations in histone H3-lysine 9 acetylation are detected around the promoter/enhancer regions of key T1D susceptible genes in monocytes of T1D subjects versus normals. Conclusion:The chromatin status of this key region is altered in T1D. Significance: Epigenetic variations at T1D susceptible genes may be functionally important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 52 publications
(64 reference statements)
1
73
0
2
Order By: Relevance
“…Analysis of public ChIP-chip microarray data of lymphocytes using anti-H4K16Ac, H3K9Ac, and H3K9me3 showed that these PTMs differentially regulated transcription of CD14, CD11c, and CD11b (53). Acetylation of H4K16 specifically increases transcription at the CD11b gene, acetylation of H3K9 specifically increases transcription at the CD14 and CD11c genes, and tri-methylation of H3K9 increases transcription at the CD11c gene but decreases transcription at the CD11b gene (supplemental Fig.…”
Section: Proper Regulation Of Histone Acetylation Is Required For Monmentioning
confidence: 99%
“…Analysis of public ChIP-chip microarray data of lymphocytes using anti-H4K16Ac, H3K9Ac, and H3K9me3 showed that these PTMs differentially regulated transcription of CD14, CD11c, and CD11b (53). Acetylation of H4K16 specifically increases transcription at the CD11b gene, acetylation of H3K9 specifically increases transcription at the CD14 and CD11c genes, and tri-methylation of H3K9 increases transcription at the CD11c gene but decreases transcription at the CD11b gene (supplemental Fig.…”
Section: Proper Regulation Of Histone Acetylation Is Required For Monmentioning
confidence: 99%
“…By profiling key epigenetic histone PTM marks in HG-treated human monocytes using ChIP-chips, we previously identified genes and chromatin regions in which histone methylation levels were altered by chronic HG as well as their correlation with gene expression (34). Using the same ChIPchip technology in peripheral blood monocytes and lymphocytes obtained from T1D patients and healthy controls, we also found genomic regions that had differential levels of several histones PTMs (31,33). Another study using next-generation sequencing reported genome-wide changes in DNA methylation and histone H3 lysine 9/14 acetylation (H3K9/K14Ac) in HG-treated human endothelial cells, which revealed several known and novel genes and pathways associated with endothelial dysfunction (38).…”
mentioning
confidence: 93%
“…Several laboratories, including our laboratory, using cell and animal models have suggested roles for key histone PTMs in high glucose (HG)-mediated effects, diabetic complications, and metabolic memory (9,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Histone PTM profiling of vascular and inflammatory cells cultured with HG vs. normal glucose (NG) or WBCs from T1D patients vs. healthy volunteers or T1D patients with complications vs. those without depicted significant PTM differences and candidate differentially methylated or acetylated genes relevant to diabetes or its complications (23,(32)(33)(34).…”
mentioning
confidence: 99%